Effects of preoperative serum lactate dehydrogenase levels on long-term prognosis in elderly patients with hepatocellular carcinoma undergoing transcatheter arterial chemoembolization - Gan, Yuantao; Gao, Fengwei; Du, Bo; Liu, Yu; Xue, Qian; Fu, Jinqiang (Frontiers in Surgery, 2022)
Hepatic arterial chemoembolization is an effective treatment for primary hepatocellular carcinoma (HCC) and can improve the survival rate of patients. Nevertheless, the long-term prognosis of patients with HCC is not optimistic. In recent years, tumor humoral detection has attracted extensive attention and is expected to become the main examination method for early tumor screening. Studies have found that serum LDH is an indicator with effective potential to predict tumor proliferation and progression, such as pancreatic cancer, esophageal cancer, nasopharyngeal cancer, etc., but the relationship between this indicator and the prognosis of HCC is still unclear. The purpose of this study was to clarify the relationship between serum LDH and the prognosis of patients with HCC, so as to provide an important scientific basis for prognosis judgment of HCC.